A 2-GHz carrier leakage calibrated direct-conversion WCDMA transmitter in 0.13-μm CMOS. - Brenna, G. (IEEE Journal of solid state circuits)
A highly integrated 2-GHz, 0.13-μm CMOS direct-conversion transmitter for wide-band code division multiple access (WCDMA) is described. Different circuit and calibration techniques are presented that successfully suppress the carrier leakage and enable the direct-upconversion architecture to meet all WCDMA specifications. The transmitter delivers +2.5 dBm output power while consuming only 45 mA from its nominal 1.5-V supply. The overall gain can be programmed in 1-dB steps over a 100-dB range with 0.4 dB accuracy. The transmitter achieves an OIP3 of +19.3 dBm, an error vector magnitude of 4.3%, and an adjacent channel leakage ratio of -38 dBc. The measured output noise of -146 dBm/Hz in the DCS Rx band and -149 dBm/Hz in the UMTS Rx band is sufficiently low to provide an option to increase the integration level even further by eliminating the external Tx interstage filter between the power amplifier and its driver.